De novo design and synthesis of an ice-binding, dendrimeric, polypeptide based on insect antifreeze proteins (2012)
A new strategy is presented for the designand synthesis of peptides that exhibitice-binding and antifreeze activity. Apennant-type dendrimer polypeptidescaffold combining an α-helical backbonewith four short β-strand branches wassynthesized in solid phase using Fmocchemistry in a divergent approach. The51-residue dendrimer was characterizedby reverse phase high performance liquidchromatography, mass spectrometry andcircular dichroism. Each β-strand branchcontained three overlapping TXT aminoacid repeats, an ice-binding motif foundin the ice-binding face of the sprucebudworm (Choristoneura fumiferana)and beetle (Tenebrio molitor) antifreezeproteins. Ice crystals in the presence ofthe polypeptide monomer displayed flat,hexagonal plate morphology, similar tothat produced by weakly active antifreezeproteins. An oxidized dimeric form of thedendrimer polypeptide also produced flathexagonal ice crystals and was capableof inhibiting ice crystal growth upontemperature reduction, a phenomenontermed thermal hysteresis, a definingproperty of antifreeze proteins. Linkageof the pennant-type dendrimer to a trifunctionalcascade-type polypeptideproduced a trimeric macromolecule thatgave flat hexagonal ice crystals withhigher thermal hysteresis activity thanthe dimer or monomer and an ice crystal burst pattern similar to that producedby samples containing insect antifreezeproteins. This macromolecule was alsocapable of inhibiting ice recrystallization.